An algorithm for combined cell-site selection and power control to maximize cellular spread spectrum capacity. - Hanly, S.V (IEEE Journal on selected areas in communications)
There is much current interest in spread spectrum wireless mobile communications and in particular the issue of spread spectrum wireless capacity. We characterize spread spectrum cellular capacity and provide a combined power control, cell-site selection algorithm that enables this capacity to be achieved. The algorithm adapts users' transmitter power levels and switches them between cell-sites, and it is shown that the algorithm converges to an allocation of users to cells that is optimal in the sense that interference is minimized. The algorithm is decentralized, and can be considered as a mechanism for cell-site diversity and handover. We provide numerical examples to show how effectively the algorithm relieves local network congestion, by switching users in a heavily congested cell to adjacent, less congested cells